Fat–fat-free index in body mass assessment in young people - Chwałczyńska, Agnieszka; Kosendiak, Aureliusz; Sobiech, Krzysztof Andrzej; Andrzejewski, Waldemar (Frontiers in Physiology, 2022)
The study aimed to personalize the classification of body weight using the fat-free fat (FFF) index with the percentage of body fat and to develop classification standards for the FFF index for men aged 18-25 years. 1,642 adolescents (1,200 ♀ ) were examined. Using body composition analyzers, weight was determined, as well as overall and segmental body composition. Based on the obtained values for fat mass and fat-free tissue mass, and overall FFF index was calculated. According to the BMI classification, 9% of ♀ and 6% of ♂ are underweight, 29% of ♀ and 13% of ♂ are overweight, and 5% of the subjects are obese. Women and men classified in the same group according to BMI differed statistically significantly in terms of body weight, FM%, and FFM. In contrast to BMI and FM%, the FFF used takes into account the ratio of fat mass to fat-free tissue and muscle tissue mass. The proposed classification of FFF was made taking into account the differences that arise with sexual development and physiological changes occurring in ontogeny. Assessment of body mass using the FFF index should be used as part of preventive screening for the early diagnosis and prevention of overweight and thus of many chronic diseases for which overweight or obesity is a risk factor.